2020
DOI: 10.11604/pamj.2020.36.268.21988
|View full text |Cite
|
Sign up to set email alerts
|

Use of tunica vaginalis graft for repair of traumatic bilateral testicular rupture after gunshot: a case report

Abstract: Bilateral testicular injuries are rare. However, the incidence of these injuries has been increasing in wartime. We describe the case of gunshot wound of the both testicle caused by high velocity bullets. The patient was managed by surgical exploration, debridement and repaired of both testis using tunica vaginalis. During the follow up, the left testis was not viable and there was a need for orchiectomy; in a follow-up of 4 months, ultrasonography showed a viable right testis with minimal atrophic change and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…It has been observed that the extent of the injury is determined by the velocity of the projectile, its structure, integrity and the distance from the gun to the target [6][7][8]14]. Thus, the higher the velocity, and the closer the target, the more extensive the injury [14][15][16]. Therefore, going by the extent of injuries observed in the two patients, it can be deduced that the guns were of the low velocity caliber (200-300 m/sec).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed that the extent of the injury is determined by the velocity of the projectile, its structure, integrity and the distance from the gun to the target [6][7][8]14]. Thus, the higher the velocity, and the closer the target, the more extensive the injury [14][15][16]. Therefore, going by the extent of injuries observed in the two patients, it can be deduced that the guns were of the low velocity caliber (200-300 m/sec).…”
Section: Discussionmentioning
confidence: 99%
“…In this series, out of three (3) testes injured, two (66.7%) were salvaged by primary repair alone. Where the testis is viable but primary approximation, due to deficiency of the tunica albuginea is not feasible, tunica vaginalis graft can be used to interpose the defect and effect a repair [15,23,25,26]. For devitalized, non-viable testes, orchidectomy is the treatment of choice.…”
Section: Fig 1 X-ray Left Thigh Showing Radio-opaque Bullet In Soft Tissuementioning
confidence: 99%